An experimental investigation on precision machining mechanism of carbon fibre reinforced polymer. (2019) - Cai, Xiaojiang; Zhou, Ruhao; Shen, Lifeng; Tang, Hongliang; An, Qinglong
With the rapid development of carbon fibre reinforced polymers (CFRPs) as main aerospace structural materials, it is necessary to manufacture CFRP structural components for high dimensional accuracy by means of precision machining. In this paper, orthogonal cutting was used to investigate machining process and surface quality of CFRP materials for precision machining. An intensive discussion was given about fibre orientation and cutting parameter range when machining CFRP for high accuracy application and optimised cutting method, including cutting speed, cutting depth, edge radius, fibre orientation, was obtained to reduce cutting force and surface roughness and get smooth surface topography. The cutting speed over 200 m/min and small cutting depth slightly large than edge radius were advisable, the fibre direction 0~45° and 90° were found suitable for precision machining. This paper provides theoretical and experimental supports for application of precision machining of CFRP materials.